Survival outcomes among periviable infants: a systematic review and meta-analysis comparing different income countries and time periods - Li, Ying Xin; Hu, Yan Ling; Huang, Xi; Li, Jie; Li, Xia; Shi, Ze Yao; Yang, Ru; Zhang, Xiujuan; Li, Yuan; Chen, Qiong (Frontiers in Public Health, 2024)
BackgroundPeriviable infants are a highly vulnerable neonatal group, and their survival rates are considerably affected by patient-, caregiver-, and institution-level factors, exhibiting wide variability across different income countries and time periods. This study aims to systematically review the literature on the survival rates of periviable infants and compare rates among countries with varied income levels and across different time periods.MethodsComprehensive searches were conducted across MEDLINE, Embase, CENTRAL, and Web of Science. Cohort studies reporting survival outcomes by gestational age (GA) for periviable infants born between 22 + 0 and 25 + 6 weeks of gestation were considered. Paired reviewers independently extracted data and assessed the risk of bias and quality of evidence. Data pooling was achieved using random-effects meta-analyses.ResultsSixty-nine studies from 25 countries were included, covering 56,526 live births and 59,104 neonatal intensive care unit (NICU) admissions. Survival rates for infants born between 22 and 25 weeks of GA ranged from 7% (95% CI 5–10; 22 studies, n = 5,658; low certainty) to 68% (95% CI 63–72; 35 studies, n = 21,897; low certainty) when calculated using live births as the denominator, and from 30% (95% CI 25–36; 31 studies, n = 3,991; very low certainty) to 74% (95% CI 70–77; 48 studies, n = 17,664, very low certainty) for those admitted to NICUs. The survival rates improved over the two decades studied; however, stark contrasts were evident across countries with varying income levels.ConclusionAlthough the survival rates for periviable infants have improved over the past two decades, substantial disparities persist across different economic settings, highlighting global inequalities in perinatal health. Continued research and collaborative efforts are imperative to further improve the global survival and long-term outcomes of periviable infants, especially those in Low- and Middle-Income Countries.Systematic review registrationPROSPERO, CRD42022376367, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022376367.